Business travel : conferences, incentive travel, exhibitions, corporate hospitality and corporate travel - Davidson, Rob, 1955-; Cope, Beulah, ....- (Harlow : Pearson education, 2003)
For all undergraduate, postgraduate and diploma students of Travel and Tourism this book provides a comprehensive, in-depth study of the business tourism market worldwide, an analysis of the relevant theoretical issues and a detailed investigation of the practice of managing and organising facilities for the business travel and tourism market. Both theoretical and practical issues are illustrated by extensive case-studies and end-of-chapter discussion questions allow students to test their knowledge and understanding.
Keywords: Zakentoerisme